Relasi Kekuasaan Legislatif dan Presiden Pasca Amandemen UUD 1945: Sistem Semi Presidensial dalam Proyeksi - Adnan Buyung Nasution (Jurnal Hukum IUS QUIA IUSTUM, 2005)
Basedon the changes to the 1945constitution, iegisiative poweris in hands of the Houseof Representatives notin the handsof Legislative Assembiy or District Representatives. In practice, almost ailpresidential powers canbesubject tointerference from theHouse of Representatives themostdangerous power possessedbytheHouse ofRepresentativesis that in making legislation the president does not possess the right of veto. Such construction can create an imbalance of powerbetween the legislative and the executive. Therefore, a semipresidential model applied bythe French can be used as an alternative modelfor the Indonesian goverment.